2011
DOI: 10.1007/s00706-011-0687-z
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of dithiocarbamates under ultrasound irradiation in water

Abstract: Multicomponent reactions with ultrasonic activation have been used as a simple, rapid, atom economic, and green method for the synthesis of dithiocarbamate derivatives in water. The one-pot, three-component condensation of primary and secondary amines with carbon disulfide and unsaturated carbonyl compounds or alkyl halides under ultrasonic irradiation was developed as a green and fast protocol for the rapid high-yielding preparation of dithiocarbamates in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…27 In the present study, we expand our search for promising antifungal agents, performing the derivatization of the conventional 2-amino acids l -alanine 2 , l -phenylalanine 3 , and l -tyrosine 4 (Figure 1) using a similar strategy to widen the available chemical space to access optimized antifungal action. Additionally, as a contribution to the green synthesis of these N , S -dialkyl dithiocarbamates, the present protocol also includes a previously reported ultrasound-assisted approach for other dithiocarbamate derivatives, 24 which importantly reduces the reaction time. Thus, this procedure can be considered attractive to synthesize these kinds of antifungal compounds since it is safer, nontoxic, cheaper, less time-consuming, and environment- and user-friendly.…”
Section: Introductionmentioning
confidence: 99%
“…27 In the present study, we expand our search for promising antifungal agents, performing the derivatization of the conventional 2-amino acids l -alanine 2 , l -phenylalanine 3 , and l -tyrosine 4 (Figure 1) using a similar strategy to widen the available chemical space to access optimized antifungal action. Additionally, as a contribution to the green synthesis of these N , S -dialkyl dithiocarbamates, the present protocol also includes a previously reported ultrasound-assisted approach for other dithiocarbamate derivatives, 24 which importantly reduces the reaction time. Thus, this procedure can be considered attractive to synthesize these kinds of antifungal compounds since it is safer, nontoxic, cheaper, less time-consuming, and environment- and user-friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different bases were screened and K 2 CO 3 was chosen as the best one (entries [6][7][8]. As for benzyl bromides, substituents ranging from weak electron-withdrawing groups, such as Br and methyl ester, to strong electronwithdrawing groups, such as NO 2 , along with electron-donating methoxyl groups, all furnished the desired benzyl diethyldithiocarbamates in good yields (entries [15][16][17][18][19][20]. The optimal reaction conditions were summarized in entry 9 and the subsequent control experiments (entries [11][12] revealed that 100°C was the most suitable temperature for benzyl bromide.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, substituted benzyl halides were treated with tetraethylthiuram disulfide (TETD) under the standard reaction conditions. As for benzyl bromides, substituents ranging from weak electron-withdrawing groups, such as Br and methyl ester, to strong electronwithdrawing groups, such as NO 2 , along with electron-donating methoxyl groups, all furnished the desired benzyl diethyldithiocarbamates in good yields (entries [15][16][17][18][19][20]. Due to the possible low reactivity of benzyl chloride, compounds 3u-3zb were obtained in moderate yields (entries 21-28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2012 年, Gholibeglo 等 [32] 利用超声的方法, 可在水 相快速地制备氨基二硫代甲酸酯类化合物. 与常规方法 相比, 超声促进的反应仅需 10 min 就能完成, 大大地缩 短了反应时间(Scheme 4).…”
unclassified